Bone conditioned media (BCM) improves osteoblast adhesion and differentiation on collagen barrier membranes. Issue 1 (December 2017) - Fujioka-Kobayashi, Masako; Caballé-Serrano, Jordi; Bosshardt, Dieter; Gruber, Reinhard; Buser, Daniel; Miron, Richard
Abstract Background The use of autogenous bone chips during guided bone regeneration procedures has remained the gold standard for bone grafting due to its excellent combination of osteoconduction, osteoinduction and osteogenesis. Recent protocols established by our group have characterized specific growth factors and cytokines released from autogenous bone that have the potential to be harvested and isolated into bone conditioned media (BCM). Due to the advantageous osteo-promotive properties of BCM, the aims of the present study was to pre-coat collagen barrier membranes with BCM and investigate its effect on osteoblast adhesion, proliferation and differentiation for possible future clinical use. Methods Scanning electron microscopy (SEM) was first used to qualitative assess BCM protein accumulation on the surface of collagen membranes. Thereafter, undifferentiated mouse ST2 stromal bone marrow cells were seeded onto BioGide porcine derived collagen barrier membranes (control) or barrier membranes pre-coated with BCM (test group). Control and BCM samples were compared for cell adhesion at 8 h, cell proliferation at 1, 3 and 5 days and real-time PCR at 5 days for osteoblast differentiation markers including Runx2, alkaline phosphatase (ALP), osteocalcin (OCN) and bone sialoprotein (BSP). Mineralization was further assessed with alizarin red staining at 14 days post seeding. Results SEM images demonstrated evidence of accumulated proteins found on the surface of collagen membranes following coating with BCM. Analysis of total cell numbers revealed that the additional pre-coating with BCM markedly increased cell attachment over 4 fold when compared to cells seeded on barrier membranes alone. No significant difference could be observed for cell proliferation at all time points. BCM significantly increased mRNA levels of osteoblast differentiation markers including ALP, OCN and BSP at 5 days post seeding. Furthermore, barrier membranes pre-coated with BCM demonstrated a 5-fold increase in alizarin red staining at 14 days. Conclusion The results from the present study suggest that the osteoconductive properties of porcine-derived barrier membranes could be further improved by BCM by significantly increasing cell attachment, differentiation and mineralization of osteoblasts in vitro. Future animal testing is required to fully characterize the additional benefits of BCM for guided bone regeneration.